Digitalization of food crop value chains: Advancing digital integration in Egypt’s key food crop value chains - Azim, Adel Abdel; Menza, Gianpiero (2025)
A consultation workshop on “Digitalization of Food Crop Value Chains: Advancing Digital Integration in Egypt’s Key Food Crop Value Chains” was held on 27 January 2025 in Cairo. The consultation aimed to advance digital solutions for Egypt’s key crops, including date palms, potatoes and tomatoes. The workshop convened more than 80 stakeholders, including government officials, researchers, AgriTech entrepreneurs, and farmers. Organized by the Alliance of Bioversity International and CIAT of CGIAR, in collaboration with the Ministry of Agriculture and Land Reclamation of Egypt, the Ministry of Higher Education and Scientific Research of Egypt, and the Innovators’ Support Fund (ISF), the workshop aims aligned with Egypt Vision 2030 to modernize agriculture through technology, addressing critical challenges to productivity, sustainability, and market access.